1999
DOI: 10.1111/j.1574-6968.1999.tb13405.x
|View full text |Cite
|
Sign up to set email alerts
|

Biocontrol of plant disease: a (Gram-) positive perspective

Abstract: Biological control offers an environmentally friendly alternative to the use of pesticides for controlling plant diseases. Unfortunately, growers continue to use chemical control over biological agents, and lack of knowledge often contributes to the downfall of a biocontrol agent. Knowledge of the biological environment in which the agent will be used and of how to produce a stable formulation are both critical to successful biocontrol. Certain Gram-positive bacteria have a natural formulation advantage over t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
192
0
11

Year Published

2003
2003
2017
2017

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 539 publications
(205 citation statements)
references
References 45 publications
2
192
0
11
Order By: Relevance
“…Screening and selection of effi cient strains and their development in suitable formulation for a particular environment are the major challenges for feasibility of this microbe based technology. While a number of Gram negative bacteria, e.g., Azotobacter, Azospirillum, Pseudomonas have received considerable attention as potential PGPR(s) [5], the bacilli are getting attention mainly due to their capability of survival under extreme environments by virtue of spore formation [6]. In the present study an efficient strain of Bacillus megaterium B388, isolated from soil samples collected from rhizosphere of pine of a temperate location in Uttarakhand Himalaya has been characterized with special reference to its plant growth promotion abilities.…”
Section: Introductionmentioning
confidence: 99%
“…Screening and selection of effi cient strains and their development in suitable formulation for a particular environment are the major challenges for feasibility of this microbe based technology. While a number of Gram negative bacteria, e.g., Azotobacter, Azospirillum, Pseudomonas have received considerable attention as potential PGPR(s) [5], the bacilli are getting attention mainly due to their capability of survival under extreme environments by virtue of spore formation [6]. In the present study an efficient strain of Bacillus megaterium B388, isolated from soil samples collected from rhizosphere of pine of a temperate location in Uttarakhand Himalaya has been characterized with special reference to its plant growth promotion abilities.…”
Section: Introductionmentioning
confidence: 99%
“…ISR by rhizobacteria was demonstrated using both Gram-negative and Grampositive bacteria (Baker et al, 1985;Maurhofer et al, 1994;Zhou and Paulitz, 1994;Liu et al, 1995;Leeman et al, 1996;Benhamou and Belanger, 1998;Pieterse et al, 1998;Kloepper et al, 2004). Bacillus subtilis not only has been reported to trigger ISR Ryu et al, 2004), but also has been implicated in promoting plant growth and protection from fungal infection (Dal-Soo et al, 1997;Emmert and Handelsman, 1999;Bacon et al, 2001;Estevez de Jensen et al, 2002;Ryu et al, 2003). Bacterial signals have been identified that activate plant defense responses through the ethylene pathway, independent of the salicylic acid (SA) pathway or the jasmonic acid pathway .…”
mentioning
confidence: 99%
“…A influência de bactérias formadoras de endosporos na sobrevivência de P. carotovorum foi estudada por Kikumoto (1980) (Emmert & Handelsman, 1999). Essas bactérias são produtoras de antibióticos, além de enzimas que degradam moléculas envolvidas no sinal de "quorum sensing" de muitas bactérias (Garbeva et al, 2004), a exemplo de B. thuringiensis no biocontrole de P. carotovorum (Dong et al, 2004).…”
Section: Para Avaliação Dos Níveis Populacionais De Pcc127unclassified